Inhalation Exposure to Atmospheric Nanoparticles and Its Associated Impacts on Human Health: A Review - Sonwani, Saurabh; Madaan, Simran; Arora, Jagjot; Suryanarayan, Shalini; Rangra, Deepali; Mongia, Nancy; Vats, Tanvi; Saxena, Pallavi (Frontiers in Sustainable Cities, 2021)
Nanoparticles (NPs) are receiving an increasing attention from many scientific communities due to their strong influence on human health. NPs are an important marker of air pollution caused by a variety of natural and anthropogenic sources. Due to their ultrafine size, they can be suspended in the atmosphere for a long time and can thus travel larger distances and cause several health issues after exposure. A variety of NPs that are found in indoor and outdoor settings cause respiratory and cardiovascular diseases. Exposure to NPs through active and passive smoking and household and occupational subjection is reported with thick septum, shortness of breath, and a high level of interleukin protein and tumour necrosis factor (TNF-α) that cause tumour generation in the exposed population. This comprehensive review summarises NPs’ source, exposure, and impact on different organ systems. Respiratory models (experimental and computational) used to determine the particle’s deposition, airflow transport, and health impact are also discussed. Further, muco-ciliary escalation and macrophage activity, the body’s clearance mechanisms after exposure to NPs, have been mentioned. An in-depth analysis of exposure to NPs through inhalation and their health impact has been provided with detailed insights about oxidative stress, inflammation, genotoxicity, and tumourigenicity. Overall, this review offers scientific evidence and background for researchers working in the field of epidemiology, biochemistry, and toxicological studies with reference to atmospheric nanoparticles.